Clutter height production technology with ArcGIS for the purposes of LTE and 5G radio network propagation and optimization - Prymak, Lidiya; Karpinsky, Yurii (Geodesy and Cartography, 2022)
The geospatial data accuracy and specification requirements for LTE and 5G radio propagation and optimization are much higher than those used in planning 2G and 3G networks. The recommended geospatial data resolution of 1–2 meters allows the display of the smallest parts of geospatial objects. In the article, we describe the technology and its practical implementation to produce an accurate clutter height (raster canopy height model) for the purposes of LTE and 5G radio network propagation and optimization. This technology, which is based on aerial images, may be adapted to use LiDAR data. The technology includes the data integration between the different software. The processing of digital terrain models, obstacles (buildings and vegetation) and DSM cloud points is performed in geographic information systems, such as ArcGIS. The technology was proven by the practical implementation and calculation in multi-technology wireless network design and optimization platform Atoll.